The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3928/1081597x-20210610-04
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Response After Corneal Cross-linking With Riboflavin Dissolved in Dextran Solution Versus Hydroxypropyl Methylcellulose

Abstract: PURPOSE: To evaluate corneal stiffening in porcine eyes induced by corneal cross-linking (CXL) using riboflavin dissolved in either aqueous dextran or hydroxypropyl methylcellulose (HPMC) solution. METHODS: Fifty-one porcine corneas were divided into three groups of 17 each. After deepithelialization, the first (Dresden) group was treated for 30 minutes with 0.1% riboflavin (riboflavin-5-monophosphate in 0.9% NaCl) dissolved in hypertonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Indeed, clinical studies have shown that the application of riboflavin/HPMC solution has little effect on corneal hydration, producing a small increase [ 23 ] or decrease [ 14 ] in corneal thickness during treatment. In tandem with the clinical findings of Zaheer et al [ 23 ] and the laboratory studies of Fischinger et al [ 28 ] on porcine corneas, this study revealed a significant increase in CCT (9%) following a 16-min application of riboflavin/HPMC to the de-epithelialised cornea. Furthermore, we showed that the post-treatment thickness of corneas that underwent CXL without a BSS rinse prior to UVA exposure, was similar to that of untreated (epithelium-removed) corneas.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, clinical studies have shown that the application of riboflavin/HPMC solution has little effect on corneal hydration, producing a small increase [ 23 ] or decrease [ 14 ] in corneal thickness during treatment. In tandem with the clinical findings of Zaheer et al [ 23 ] and the laboratory studies of Fischinger et al [ 28 ] on porcine corneas, this study revealed a significant increase in CCT (9%) following a 16-min application of riboflavin/HPMC to the de-epithelialised cornea. Furthermore, we showed that the post-treatment thickness of corneas that underwent CXL without a BSS rinse prior to UVA exposure, was similar to that of untreated (epithelium-removed) corneas.…”
Section: Discussionsupporting
confidence: 83%
“…Oxygen depletion has been proposed as a reason for the formation of new covalent junctions [26,27]. Many authors argue that the medium in which Rb is delivered is essential to shorten the exposure time and improve the cost-effectiveness of CXL [28,29]. In the current study, the performance of VibeX Rapid® was superior to that of the other formulations.…”
Section: Discussionmentioning
confidence: 60%
“…Compared with dextran riboflavin, HPMC riboflavin might present improved CXL effect resulted from enhanced concentration of riboflavin in the cornea and a deeper demarcation line (Malhotra et al, 2017;Thorsrud et al, 2019). Nevertheless, dextran riboflavin might result in slightly stronger biomechanical properties and better visual outcomes (demonstrated by visual acuity) (Rapuano et al, 2018;Fischinger et al, 2021). As for safety, HPMC riboflavin performed as well as dextran riboflavin (De Paula et al, 2020).…”
Section: Dextran and Hydroxypropyl Methylcellulose (Hpmc)mentioning
confidence: 99%